FINANCIAL PERFORMANCE AND EFFECTIVENESS ON DEBT MANAGEMENT IN STATE-OWNED ENTERPRISE PHARMACEUTICAL SECTOR PERIOD 2004 - 2016 - Andi Dewi Angreyani (Department of Management FEB Unhas, 2018)
This study aims to determine the effect of financial performance, effectiveness, corporate growth on debt management in state-owned enterprises in the pharmaceutical sector period 2004 to 2016.The object of this research is state-owned pharmaceutical company. Financial performance with ROI, ROE and NPM as indicator, effectiveness with CR as indicator and company growth (GROWTH as indicator) is independent variable, while debt management with DAR as indicator. The sampling technique used is purposive sampling with audited financial statement criteria and published from 2004 to 2016 and has a book year ended on 31 December. Earned 39 samples from 3 state-owned enterprises Pharmaceutical Sector.Data analysis techniques using PLS-SEM by testing outer and inner. Data is then processed with SmartPLS 3.0 software.The results obtained are the financial performance and effectiveness have a positive and significant influence on debt management while the growth of the company has no positive and significant influence on the management of debt in state-owned pharmaceutical secktor company. Keywords: Financial Performance, Effectiveness, Corporate Growth Profit Growth, Debt Management.